The Effect of Capital Adequacy Ratio, Loan to Deposit Ratio, Operating-Income Ratio, Non Performing Loans, Net Interest Margin on Banking Financial Performance - Refni Sukmadewi (eCo-Buss, 2020)
The weak condition of the banking sector encourages those involved in conducting a bank health assessment. One of the parties is the investor because the better the bank's performance, the greater the security guarantee of the invested funds. By using financial ratios, investors can find out the performance of a bank that can be seen through various variables. The variable used as the basis for valuation is the financial statements of the companies concerned. Company performance can be measured by analyzing and evaluating financial statements. Information on financial position and performance in the past is often used as a basis for predicting financial position and performance in the future. Banking performance can be measured using average loan interest rates, average deposit interest rates, and bank profitability. The profitability measure used is return on assets (ROA) in the banking industry. Return on Assets (ROA) focuses the company's ability to obtain earnings in the company's operations. The reason for choosing Return on Assets (ROA) as a measure of performance is because Return on Assets (ROA) is used to measure the effectiveness of the company in generating profits by utilizing its assets. The greater ROA shows the better financial performance, because the greater the rate of return. This study aims to examine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating-Income Expense Ratio (BOPO), Non Performing Loans (NPL), Net Interest Margin (NIM), and on Return on Assets (NIM) ROA) as the Financial Performance of Banking Companies Listed on the Indonesia Stock Exchange in 2016-2018. The data used in this study were obtained from the Annual Financial Statements of Banking Companies Listed on the Stock Exchange in 2016-2018. the samples used were 23 Banking Companies Listed on the IDX. The analytical method used is multiple linear regression. The results showed that the CAR, BOPO, NPL, NIM, and LDR variables had a positive and significant effect on Return on Assets (ROA). Thus the bank is expected to pay attention to the level of efficiency of its operations to increase profitability on its financial performance.